“Salvemos os nossos índios”: uma catequese dominicana no Araguaia (1922-1933): "Let’s save our Indians": a Dominican catechism in Araguaia (1922-1933) (Revista de História da UEG (REVHIST), 2019)
Abstract: This article analyzes the discursive practice of the Dominican priests after the creation of their catechism of Conceição do Araguaia, having as a source the magazine Cayapós e Carajás (RCC), edited between 1922 and 1933. It is part of the enunciation "let’s save our Indians ", a missionary representation of the natives as "savages", passive of an action civilization and, therefore, pacificatory. In an attempt to "save the soul" of the natives, the dominicans repeatedly proclaimed heralds of "faith" and the "salvation", a narrative elaborated during the historical context in which interethnic relations took place. The enunciation of evangelizing missionary activity, present in the magazine, continued naming, classifying, labeling and "inventing" the other as "savage", "brave" or "tamed". Thus, it was incumbent upon the civilizing project of the Church and its allies to "educate", evangelize, "pacify" the natives, considered as "pagan souls" living "in the darkness of death" in "a desert of souls". They aid in the examination of religious discursive practice the theoretical formulations of Bakhtin (2006) and Orlandi (1990), through the representations of incorporation or denial of the other by the attribution of "ideological signs" proper to an especific cultural sphere.